All Days 2012
DOI: 10.2118/152351-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Approach to Production Stimulation of Massive Cold Heterogeneous Carbonate Formation using Coiled Tubing

Abstract: The Orenburg oil, gas and condensate field (OOGCF) is one of the largest fields in the Volgo-Urals region of Russia. It is characterized by complex formation lithology, underlying water, low bottomhole temperature and significant reservoir depletion making successful matrix acidizing particularly challenging. Existing wellbore equipment prohibits the use of inflatable packers. Therefore only chemical diverters can be used for treatments. Thorough engineering and previous acidizing experience in this region lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…After the spearhead, the normal matrix acidizing treatment continued with alternating stages of acid and chemical diverter. Dnistryansky et al (2012) showed an example of using VSD spearhead stages during matrix acidizing of the giant Orenburg oil, gas, and condensate field. While previous acidizing treatments on the field had caused water breakthrough, no water production was observed on wells treated with the spearhead VSD stage.…”
Section: Viscoelastic Selective Divertermentioning
confidence: 99%
See 3 more Smart Citations
“…After the spearhead, the normal matrix acidizing treatment continued with alternating stages of acid and chemical diverter. Dnistryansky et al (2012) showed an example of using VSD spearhead stages during matrix acidizing of the giant Orenburg oil, gas, and condensate field. While previous acidizing treatments on the field had caused water breakthrough, no water production was observed on wells treated with the spearhead VSD stage.…”
Section: Viscoelastic Selective Divertermentioning
confidence: 99%
“…CT is available in the Volga-Urals region and high friction pressure limits the maximum pump rate to 150 L/min. Dnistryansky et al (2012) showed that in long openhole carbonate intervals matrix acidizing with 15% HCl through 1.5-in. CT results in face dissolution but no wormholes (Fig.…”
Section: Using Ct For Matrix Acidizingmentioning
confidence: 99%
See 2 more Smart Citations